Inhibition of Plasmodium falciparum growth by IgG antibody produced by human lymphocytes transformed with Epstein-Barr virus. - Brown, J; Whittle, H; Berzins, K; Howard, R; Marsh, K; Sjoberg, K (1986)
Supernatants from Epstein-Barr virus (EBV)--stimulated B lymphocytes obtained from two adult Gambians who were partially immune to malaria markedly inhibited the growth of Plasmodium falciparum in vitro (55-95% inhibition). When 22 separate colonies were derived by micromanipulation from one of these primary cultures and their supernatants assayed, the degree of inhibition correlated with levels of IgG fluorescent antibody and total IgG. The inhibitory anti-P. falciparum IgG immunoprecipitated an antigen of mol. wt 195,000, identified as the major schizont surface glycoprotein by dual biosynthetic labelling with 3H-glucosamine or 35S-methionine. Other studies on the analogous schizont surface protein of rodent malarias have shown that this antigen stimulates protective immunity. Production of this inhibitory antibody by adult Gambians may therefore contribute to their immunity to malaria. Human antibodies produced by EBV-stimulated B lymphocytes may be used to identify other important P. falciparum antigens and have potential applications for immunotherapy.